Stress of nursing professionals working in pre-hospital care - Ana Elizabeth Lopes de Carvalho; Iracema da Silva Frazão; Darine Marie Rodrigues da Silva; Maria Sandra Andrade; Selene Cordeiro Vasconcelos; Jael Maria de Aquino (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: To analyze the factors related to the occupational stress of a Mobile Emergency Care Service (Samu) nursing team. Methods: This is a descriptive study, with a quantitative approach, performed with nursing professionals from Samu service of a city of Pernambuco. A sociodemographic questionnaire and the Lipp's Stress Symptom Inventory were used. Results: The participants presenting stress (24.6%) were classified in the phases: resistance (19.7%), exhaustion (4.4%) and near exhaustion (0.5%). It was also observed an association of stress level with the following factors: gender, sleep quality, professional autonomy restriction, emotional exhaustion with work performed and work in inadequate or unhealthy physical facilities. Conclusions: Although showing low occurrence of stress, this study pointed out the profile that presents the highest risk of developing occupational stress, through the factors significantly associated with stress in the studied population.